Pemutakhiran Kebijakan Smart Health City Secara Kolaboratif Sebagai Upaya Pelaksanaan Revolusi Mental: Studi Di Kota Depok - Adam Dwi Juliansyah; Dyah Ayu Febriani; Hisyam Yusril Hidayat; Mohammad Hernanda Trianggoro; Vanissa Noorizqa Prastowo (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2020)
The problem in the health sector is one of the complicated problems faced by the government, this is evidenced by the extraordinary events (KLB) in various regions, one of which is the Hepatitis A outbreak in Depok that accumulates 306 cases. The main cause of these outbreaks is the low awareness and mentality of the public regarding the application of healthy and clean lifestyles and the government's preventive ability in terms of policies. Seeing this problem, the City Government of Depok has a strategic plan in the form of the Smart Healthy City (SHC) Depok policy as one of the policy efforts in order to improve the quality of public health through implementing technology and increasing competence in realizing the policy. This paper aims to review how the SHC Depok strategic plan policy can be collaboratively updated to carry out a mental revolution not only at the local government level, but also that policy can be understood by the public. The goal of the mental revolution is not only towards society, but also from the side of the government and various other parties. This paper was compiled from primary data in the form of in-depth interviews with various informants and secondary data from books, journals, and electronic sources. The expected outcome of the SHC Depok policy renewing itself is to improve the quality of services and improve the quality of public health based on preventive and collaborative actions.